PENGARUH SUBSTITUSI TEPUNG SELPIS (SELUANG DAN PISANG) TERHADAP KADAR PROTEIN, KALSIUM, DAYA TERIMA DAN MUTU ORGANOLEPTIK COOKIES - Ayu Sagita Putri; Mars Khendra Kusfriyadi; Agnescia Clarissa Sera (JURNAL RISET GIZI, 2020)
Background: Insufficiency of nutrients intake such as protein and calcium may lead to the incidence of stunting in children under five years. In fact, Indonesia has many local foods like freshwater fish and local fruits which had abundant nutrients. Seluang is a typical Kalimantan freshwater fish contains high protein and calcium. The utilization of seluang fish flour and kepok banana flour as substitution in making cookies will increase the nutritional value of protein and calcium and may reduce the use of wheat flour.Objective: This study aims to analyse the effect of selpis (seluang and banana) flour substitution on protein, calcium, acceptability and organoleptic quality of cookies.Method: Experimental method with a completely randomized design (CRD) with five flour substitution treatments: 0%, 5%, 10%, 15%, 20% was used in this study. The protein content was tested by Kjeldahl method while the calcium content was tested by the AAS method.Results: Most of panelists preferred the original cookies (P1), characterized by yellowish in colour, fresh-baked aroma, slightly tough in texture and sweet-taste. The highest levels of protein and calcium were at P5 (20%) of 12.25% and 5.88 mg / 100 g.Conclusion: The substitution of seluang and kepok banana flours affect protein levels, calcium levels, acceptability (taste, color and aroma) of cookies but does not affect the texture of cookies.